Утилізація відходів у ливарному виробництві - Іванова, Л.Х. (Physico-technological Institute of Metals and Alloys, 2023)
The results of laboratory studies on the use of various wastes, that have not previously been used for alloying cast irons, are given. The use of wastes allowed to improve the properties of cast irons and to increase the rate of mastering of alloying elements in comparison with the use of ferroalloys.